Ruminal Acidosis Part I: Clinical manifestations, epidemiology and impact of the disease - Voulgarakis, N; Gougoulis, D; Psalla, D; Papakonstantinou, G; Angelidou-Tsifida, M; Papatsiros, V; Athanasiou, LV; Christodoulopoulos, G (Journal of the Hellenic Veterinary Medical Society, 2023)
Abstract Ruminal acidosis is presented as the most considerable nutritional disorder of ruminants with severe impacts in animal health, animal welfare and considerable economics losses in ovine and bovine herds. The disease can be distinguished as Acute (ARA) and Sub-Acute Ruminal Acidosis (SARA). SARA constitutes as the main nutritional disorder in intensive ruminant farming with several complications, such as liver abscesses, milk fat depression, reduced milk yield and early culling. This paper constitutes the first part of a thorough review about ruminal acidosis. The first part focuses on definition, types of ruminal acidosis, epidemiology, economic impacts and welfare implications.